Investigation of African swine fever outbreaks in pigs outside the controlled areas of South Africa, 2012–2017 - (:unkn) unknown (My University, 2020)
South Africa historically experienced sporadic African swine fever (ASF) outbreaks in domestic pigs in the northern parts of the country. This was subsequently indicated to be because of spillover from the sylvatic cycle of ASF between warthog and tampans (soft ticks) in the area. South Africa declared this area an ASF-controlled area in 1935, and the area is still controlled in terms of the Animal Diseases Act, 1984 (Act 35 of 1984). Two main epidemics of ASF in domestic pigs were identified outside of the South African ASF-controlled area. The first occurred in 2012 with outbreaks in Gauteng and Mpumalanga provinces, and the second occurred in 2016-2017 with outbreaks in the North West, Free State and Northern Cape provinces. These were the first ASF epidemics in South Africa associated with transmission of the disease via a domestic cycle. This study found that the spread of ASF in these epidemics was mainly via auctions, swill feeding and scavenging. These three aspects need to be addressed in terms of awareness and education on the disease including implementation of biosecurity measures in order to prevent future ASF outbreaks in South Africa. Specific biosecurity measures should be implemented in the semi-commercial sector to prevent ASF-infected pigs and pig products from being moved to naive pigs and therefore spreading the disease.
Keywords: African Research